2019
DOI: 10.24059/olj.v23i2.1488
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a Sense of Belonging in Online Learning Communities of Inquiry

Abstract: A sense of belonging (SoB) is a valued concept in campus-based learning, being firmly linked with improved student attainment, increased learners’ satisfaction and reduced attrition rates. Some researchers even assert that learners are unable to fulfil the goals of higher education without acquiring a SoB.  This article recognises that SoB can help promote and consolidate learning and seeks to specify how tutors may nurture online learners’ SoB. An adapted version of the Community Inquiry Framework (CoIF) is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 23 publications
2
60
0
1
Order By: Relevance
“…In line with Berry's (2019) recommended strategies, educators used synchronous class meetings to address academic content and provide outlets for personal sharing, in some cases allowing younger students to participate in virtual community circles. By responding to students' need for more informal synchronous peer interactions, educators helped foster the peer relationships vital to students' sense of school belonging (Peacock & Cowan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In line with Berry's (2019) recommended strategies, educators used synchronous class meetings to address academic content and provide outlets for personal sharing, in some cases allowing younger students to participate in virtual community circles. By responding to students' need for more informal synchronous peer interactions, educators helped foster the peer relationships vital to students' sense of school belonging (Peacock & Cowan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even though students would want to non-belong, educators might still have the responsibility to promote collaboration and sense of belonging, since the students' own will might not always represent what is best for them (which goes back to the core of what is meant by education -educators also want to correct unfunctional study strategies, for example). Earlier research has highlighted the affordances that online systems offer for sense of belonging, even when students would only be able to attend their courses remotely (Peacock and Cowan 2019), which offers an interesting perspective for mathematics communities. However, even more important is to promote teaching practices that prevent unbelonging and structural alienation (see Solomon 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has also shown that active learning environments in higher education offer an affordance for fostering social interaction and collaboration (Clinton and Wilson 2019;Theobald et al 2020;Lahdenperä et al 2019). Furthermore, both formal and informal student interaction during study at university has been connected with increased sense of belonging (Masika and Jones 2016;Meeuwisse et al 2010;Peacock and Cowan 2019;Thomas 2012). The role of teaching practices has been shown to be central in sense of belonging in mathematics as well.…”
Section: Introductionmentioning
confidence: 99%
“…Garrison (2011) articulates the importance of belonging in online communities of inquiry, stating that we should "establish a feeling of belonging to the critical community that must develop over time" (p. 32). The authors (Peacock & Cowan, 2019) have used an adapted version of the community inquiry framework to frame specific suggestions for action to nurture online learners' sense of belonging.…”
Section: Belonging In Online Learningmentioning
confidence: 99%